Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1088/1361-6595/ab62dc
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distributions of plasma potential and density in electron cyclotron resonance ion source

Abstract: The Numerical Advanced Model of Electron Cyclotron Resonance Ion Source (NAM-ECRIS) is applied for studies of the physical processes in the source. Solutions of separately operating electron and ion modules of NAM-ECRIS are matched in iterative way such as to obtain the spatial distributions of the plasma density and of the plasma potential. Results reveal the complicated profiles with the maximized plasma density close to the ECR surface and on the source axis. The ion-trapping potential dips are calculated t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 25 publications
0
14
1
Order By: Relevance
“…The density profile is almost uniform inside the ECR volume, with formation of the small local density maxima close to the ECR surface for the largest gas flow. These maxima are much less pronounced in comparison to what had been reported in our previous publication [4], where the electron dynamics was calculated in assumption that electrons do not interact with microwaves inside the ECR volume.…”
Section: Modelling Of the Electron Dynamicscontrasting
confidence: 71%
See 2 more Smart Citations
“…The density profile is almost uniform inside the ECR volume, with formation of the small local density maxima close to the ECR surface for the largest gas flow. These maxima are much less pronounced in comparison to what had been reported in our previous publication [4], where the electron dynamics was calculated in assumption that electrons do not interact with microwaves inside the ECR volume.…”
Section: Modelling Of the Electron Dynamicscontrasting
confidence: 71%
“…The ECR positions are labeled with the dashed lines. The field amplitudes close to the resonance are at the level of ~10 4 V/m and decrease by a factor of 2 inside the ECR zone. Standing wave patterns are seen both inside and outside the zone regions.…”
Section: Modelling Of the Microwave Propagation In The Source Plasmamentioning
confidence: 95%
See 1 more Smart Citation
“…The spatial distribution of hot electrons in ECRIS plasmas has been studied both numerically and experimentally [34][35][36] and it has been concluded that the majority of the plasma energy content is carried by the electron population in the dense plasmoid surrounded by the ECR surface. As the instabilities are driven by the local EED, it could be argued that the volume by the resonance zone therefore affects the B min at the instability threshold.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, they obtained a great degree of match between predicted and measured steady-state CSD and were able to analyze various aspects of ECRIS operation such as neutral density gradient and isotope anomaly effect. In later works, they extended their analysis to include multicomponent, localized electron energy distribution functions and investigated the ion confinement processes in the plasma [20] and then applied their algorithms to investigate the behavior of the device with different working materials [21]. The local neutrality assumption was dropped by coupling an electron simulation code NAM-ECRIS(e) with its ion counterpart NAM-ECRIS(i), effectively modeling electron and ion evolution simultaneously in the plasma [22].…”
Section: Ecr Simulation Models: a Reviewmentioning
confidence: 99%